Livestock rearers socio-economic status, feed resources, feeding and management practices in Gurez valley of Kashmir - BEIGH, YASIR AFZAL; GANAI, ABDUL MAJEED; RATHER, MOHAMMAD ASHRAF; FAZILI, MUJEEB; HUSSAIN, HAKIM ATHAR; MALIK, ASLOOB AHMAD; RAJA, TARIQ AHMAD; MIR, SHAHID HASSAN (The Indian Journal of Animal Sciences, 2021)
The study was undertaken to assess the socio-economic status of animal rearers, available feed resources and feeding and management practices of livestock at different zones in Gurez valley of Kashmir. A baseline survey was conducted to obtain the information in three arbitrary zones, viz. lower, middle and upper Gurez. The study was carried out in three villages in each zone where seven farmer families per village were selected randomly for the study. A total of 63 households owning livestock were interviewed using a pre-tested structured questionnaire and through direct observation. Majority of the farmers’ families was joint (94%), fell under middle age category (41%), had small land holdings (37%) and was predominantly illiterate (28%) but all categorised under Schedule Tribe. Animal husbandry (20%) was the major occupation after household (31%). Monthly income level was adequate. Among different livestock species reared, small ruminants (sheep and goat) were predominant (55%) although the productivity was low. Almost all the farm produce was consumed locally. Maize stover and forest grass hay were the main sources of dry roughages, while natural grazing was the main and important green forage source during summers. Concentrates were mainly home-made (87%) prepared without the use of oilcakes. The chemical composition of the available feed resources were within the normal ranges. The animals were left for grazing during summers with no concentrate supplementations (81%); however were offered lopped tree foliage (92%). During winters, livestock were completely stall fed primarily on crop residues with no or little concentrate mixture supplementation (86%) being offered only to lactating or pregnant animals. Majority of the farmers (94%) did not supplement the diet of animals with mineral mixture. Semi-migratory (89%) and stationary (11%) were the two types of animal production system being practiced. All the farmers (100%) had kacha close type of houses for their animals, mainly as part of human dwellings (94%). Animal stockings within the sheds were mostly mixed (89%) with little provision for proper ventilation (9%) and no (0%) regular bedding and drainage arrangements. Sanitary conditions of majority of the livestock farmers were poor with below average technical knowledge about livestock farming (67%). From results of this study, it could be concluded that to ensure sustainable livestock production in the surveyed area, technological, technical and institutional innovations would be vital to overcome the constraints of feed/fodder scarcity and lack of scientific knowledge.